KAJIAN LUAS PETAK TEBANG OPTIMAL DI HUTAN TANAMAN RAWA GAMBUT: KASUS DI SATU PERUSAHAAN HUTAN DI RIAU - Sona Suhartana; Sukanda; Yuniawati (BRIN Publishing, 2012)
Productive and effective logging activities are usually contentrated at the felling site. These mean that an ideas, felling site development at peat swamp forest plantation in determined by an optimum area. There has been limited study on optimum felling site area at peat swamp forest plantation in Indonesia. This study was carried out in June 2011 at concession area of Arara Abadi Company, Riau. This study aimed of finding out optimum felling site area at peat swamp forest plantation. Field data from some alternatives felling site area i.e. productivity and cost of skidding and canal maintenance/development were collected and processed by tabulation. Study result revealed that based on technique and cost aspects felling site of 150 m x 350 m is an optimum size.